A Modified Technique Reduced Operative Time of Laparoendoscopic Rendezvous Endoscopic Retrograde Cholangiopancreatography Combined with Laparoscopic Cholecystectomy for Concomitant Gallstone and Common Bile Ductal Stone. (15th June 2014) - Liu, Wei; Wang, Qunwei; Xiao, Jing; Zhao, Liying; Huang, Jiangsheng; Tan, Zhaohui; Li, Pengfei
Abstract : Laparoendoscopic rendezvous (LERV) endoscopic retrograde cholangiopancreatography (ERCP) and laparoscopic cholecystectomy (LC+ERCP/LERV) are considered an optimal approach for concomitant gallstones and common bile duct stones. The rendezvous technique is essential for the success of procedure. We applied two different LERV techniques, traditional technique and modified technique, in 60 consecutive cases from January 2011 to November 2012. 32 cases who underwent modified technique (group 1) from February 2012 to November 2012 were retrospectively compared to 28 cases (group 2) who underwent traditional technique from January 2011 to January 2012. There was no significant difference between two groups with respect to preoperative demographic features. Although the difference was not statistically significant, the procedure was successfully performed in 31 cases (96.9%) in group 1 and 24 cases (86.2%) in group 2. The mean operative time and time of endoscopic part were 82.6 ± 19.6 min and 26.5 ± 5.99 min in group 1 which were significantly shorter than those in group 2 (118.0 ± 23.1 min and 58.7 ± 13.3 min, resp.). There was no postoperative pancreatitis and mortality in both groups. The mean hospital stay, blood loss, incidence of complications, and residual stone were of no difference in both groups. This study proved that this modified technique can effectively reduce the operative time and time of endoscopic part of LC+ERCP/LERV compared with traditional technique.